Lightweight high strength panel for green wall - Teo, Hazel Hui Ting (Nanyang Technological University, 2021)
Interest in vertical greening systems have soared in recent years due to the increasing environmental awareness and sustainable architectural movement. However, the expensive installations and the possible long-term maintenance required have found reluctancy amongst building developers to adopt such technology despite its appreciable benefits in energy savings and support to the urban ecology. The development of a more cost-effective green walls panel specifically its growing medium used will be the objective for this project. 2 prototypes of different growing medium materials were studied: Melamine Foam (Prototype 1) and Melamine Foam + Floral Foam (Prototype 2). Commonly used plant species in green walls and other low maintenance plant varieties were used as indicator plants to evaluate its performance as well. The growth of these plants was observed over a period of 6 months to a year and results have showed that plants in Prototype 1 did not survived well due to issues with poor water distribution in the Melamine Foam medium. Prototype 2, on the other hand, had showed promising results supporting a wide range of plants to achieve the desired aesthetics of a green wall. Designs proposed in Prototype 2 had not only resolved issues faced in Prototype 1, efficiency in water usage had also improved and transplantation process was very much simplified as well – potentially reducing the time and cost incurred for installation. The combined use of Melamine Foam and Floral Foam as a growing medium is thus a probable solution for a more sustainable and cost-effective green wall.